(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Research on the effect of dry extract “Thang thanh giang troc” on some blood indicators of rats in the model of chronic kidney disease with 5/6 rat nephrolysis. Subject and method: Evaluation of the effect of dry extract of “Thang thanh giang troc” on some blood indices of male Wistar white rat. Subjects: White Wistar rats, male, adult, healthy, weight from 200 - 250g. Experimental rats were provided by the Animal Department - Military Medical Academy. Method: Research the effect of dry extract "Thang thanh giang troc" on the model of chronic kidney disease with 5/6 kidney resection in rats. Results: After 60 days of taking the dried extract “Thang Thanh Giang Troc” Compared with the model batch, the serum urea concentration of mice in the drug-treated groups decreased significantly with p < 0.01. The serum urea concentration of mice in the Thang thanh giang troc 2 (TTGT-2) group decreased the most, and was statistically significantly different from that in the Thang thanh giang troc 1 (TTGT-1) group (p < 0.05). Compared with the model batch, the serum creatinine concentration of mice in the drug-treated groups decreased significantly with p < 0.01. The serum creatinine concentration of mice in the TTGT-2 group decreased the most, and was statistically significantly different from that in the TTGT-1 group (p < 0.05). Compared with the model batch, the number of red blood cells in mice and the hemoglobin content of mice in the drug-treated groups increased, and was statistically significantly different from that in the TTGT-1 group (p < 0.05). The difference in hematocrit of mouse blood between different batches was not statistically significant (p > 0.05). Conclusion: The dry extract of "Thang Thanh Giang Troc" at various doses has shown the effect of reducing serum urea and creatinine concentrations, increasing hematological indices of mice in a mouse model of chronic kidney disease.